Outcomes of a Specialized Interdisciplinary Approach for Patients with Cancer with Aberrant Opioid‐Related Behavior. (27th October 2017) - Arthur, Joseph; Edwards, Tonya; Reddy, Suresh; Nguyen, Kristy; Hui, David; Yennu, Sriram; Park, Minjeong; Liu, Diane; Bruera, Eduardo
Abstract : Background: Data on the development and outcomes of effective interventions to address aberrant opioid‐related behavior (AB) in patients with cancer are lacking. Our outpatient supportive care clinic developed and implemented a specialized interdisciplinary team approach to manage patients with AB. The purpose of this study was to report clinical outcomes of this novel intervention. Materials and Methods: The medical records of 30 consecutive patients with evidence of AB who received the intervention and a random control group of 70 patients without evidence of AB between January 1, 2015, and August 31, 2016, were reviewed. Results: At baseline, pain intensity ( p  = .002) and opioid dose ( p  = .001) were significantly higher among patients with AB. During the course of the study, the median number of ABs per month significantly decreased from three preintervention to 0.4 postintervention ( p  < .0001). The median morphine equivalent daily dose decreased from 165 mg/day at the first intervention visit to 112 mg/day at the last follow‐up ( p  = .018), although pain intensity did not significantly change ( p  = .984). "Request for opioid medication refills in the clinic earlier than the expected time" was the AB with the highest frequency prior to the intervention and the greatest improvement during the study period. Younger age ( p  < .0001) and higher Edmonton Symptom Assessment System anxiety score ( p  = .005) were independent predictors of the presence of AB. Conclusion: The intervention was associated with a reduction in the frequency of AB and opioid utilization among patients with cancer receiving chronic opioid therapy. More research is needed to further characterize the clinical effectiveness of this intervention. Implications for Practice: There are currently no well‐defined and evidence‐based strategies to manage cancer patients on chronic opioid therapy who demonstrate aberrant opioid‐related behavior. The findings of this study offer a promising starting point for the creation of a standardized strategy for clinicians and provides valuable information to guide their practice regarding these patients. The study results will also help clinicians to better understand the types and frequencies of the most common aberrant behaviors observed among patients with cancer who are receiving chronic opioid therapy. This will enhance the process of timely patient identification, management, or referral to the appropriate specialist teams. Abstract : This article reports the outcomes of a comprehensive specialized interdisciplinary team intervention that was designed to help manage patients with cancer with aberrant opioid‐related behavior.